Równania Cauchy’ego-Riemanna i przekształcenia konforemne - Florek, Jan (Cauchy-Riemann equations and conformal maps, 2009)
We consider relations between the existence of a complex derivative for a complex function f and the existence of a tangent function L(z) = az = bz to f, which preserves angles in the point 0, as well as relations with the Cauchy-Riemann equations. We discuss also properties of some conformal maps on the plane
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 33-42
Keywords: complex derivative; Cauchy-Riemann equations; conformal map; exponential function; homographic function